Zastosowanie metody wypłukiwania gazów w diagnostyce czynnościowej płuc u dzieci - Wawszczak, Maria; Peradzyńska, Joanna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
The inert gas washout (IGW) is a noninvasive measurement applicable in evaluation of peripheral airway function. This technique offers information about pulmonary ventila¬tion inhomogeneity and provides insight into the evolution of pathological processes by assessing the efficiency of inert gases washout. The method can be performed by two techniques: single breath washout (SBW) test which involves a vital capacity maneuvers and over a series of tidal breathes termed a multiple breath washout test (MBW). The utility of IGV was demonstrated in diagnosis and management of chronic pulmo¬nary conditions particularly in cystic fibrosis and asthma. It is characterized by a higher sensitivity than spirometry in detecting early lung function abnormalities. Despite this, the widespread application of IGW in clinical setting is limited by poor availability of devices and lack of clearly defined international recommendation for the interpretation of the results. The article represents a theoretical background and clinical utility of this method.